Nitrogen physical optimum rate for hybrid and open-pollinated maize varieties under Chitwan conditions - Khatri, Krishna; Ojha, Roshan Babu; Bhusal, Jhabnath (Nepal Agriculture Research Journal, 2025)
Nitrogen (N) is a critical limiting nutrient, and its optimization is essential for sustainable maize production. Pipeline maize varieties developed at the National Maize Research Program (NMRP) require evaluation of nitrogen application rates based on their production potential. This study was conducted in the research fields of NMRP during 2022 and 2023 to optimize nitrogen rates for two pipeline maize varieties: a hybrid variety (CAH1511) and an open-pollinated variety (ZM627). This field experiment utilized a Randomized Complete Block Design (RCBD) with eight nitrogen application rates, each replicated three times. The physical optimum nitrogen rate was determined through the first derivative of the quadratic yield function, using pooled data and yield correction methods. In 2022, the hybrid maize demonstrated the highest grain yield (10.93 t/ha) at a nitrogen application rate of 200 kg/ha, which was statistically comparable to yields achieved with 240, 160, and 120 kg N/ha. The lowest yield (4.45 t/ha) was recorded in the nitrogen omission plot. In 2023, the hybrid maize achieved its highest mean yield (14.85 t/ha) at 200 kg N/ha, whereas the lowest mean yield (3.50 t/ha) was observed in the nitrogen omission plot. For the open-pollinated maize, the highest grain yield in 2022 (8.61 t/ha) was recorded at 160 kg N/ha, which was statistically similar to yields at 240 and 120 kg N/ha. The lowest yield (3.80 t/ha) occurred in the 0 kg N/ha nitrogen omission plot. In 2023, the highest grain yield (9.91 t/ha) for open-pollinated maize was obtained with 240 kg N/ha, which was at par with 60 kg N/ha, while the lowest yield (3.80 t/ha) was again observed in the nitrogen omission plot. A significant correlation was observed between grain yield and key yield attributes for both maize types, including plant height (r = 0.782, p < 0.001), cob length (r = 0.964, p < 0.001), cob diameter (r = 0.836, p < 0.001), number of rows (r = 0.508, p < 0.001), number of grains per row (r = 0.951, p < 0.001), and thousand-grain weight (r = 0.630, p < 0.001). The pooled quadratic regression analysis revealed that the physical optimum nitrogen rate was 216 kg N/ha for hybrid maize and 164 kg N/ha for open-pollinated maize. In conclusion, the study demonstrates that hybrid and open-pollinated maize varieties respond differently to nitrogen fertilizer, with distinct optimum nitrogen rates. These findings can contribute to minimizing nitrogen loss, preventing yield reductions in maize, and promoting environmental sustainability.